Detection and location of open-circuit fault for modular multilevel converter. (February 2020) - Hu, Xing; Zhang, Jianzhong; Xu, Shuai; Deng, Fujin
Highlights: The open-circuit fault of switch in MMC affects the full arm voltage. The open-circuit fault of switch in MMC also affects the capacitor voltage. Fault can be diagnosed based on extended state observer and tracking differentiator. The change rate of full arm voltage in MMC could be used to detect the fault. The change rate of capacitor voltage in MMC could be used to locate the fault. Abstract: Modular Multilevel Converter (MMC) is one of the most promising converters in high voltage applications. However, the large number of submodules and power switching devices make the MMC susceptible to failure. The faulty power switching device should be detected and located rapidly to avoid further faults on the MMC system. This paper proposes an extended state observer (ESO) based open-circuit fault detection and location method. The theoretical and observed full arm voltage is calculated by the calculator and ESO, respectively. Then the difference differential between the theoretical and observed full arm voltage is used to detect the fault. The change rate of the capacitor voltages in different submodules is acquired to locate the faulty submodule. During the fault detection and location period, the tracking differentiator (TD) algorithm is used to obtain the value of change rate. The effectiveness of the proposed fault diagnosis strategy is validated by the simulation and experiment results.